Left Atrial Remodeling and Recurrence of Congestive Heart Failure in Patients Initially Diagnosed with Heart Failure. Issue 8 (24th December 2013) - Yamaguchi, Kazuto; Yoshitomi, Hiroyuki; Ito, Shimpei; Ito, Saki; Adachi, Tomoko; Sato, Hirotomo; Watanabe, Nobuhide; Kodani, Nobuhiro; Sugamori, Takashi; Endo, Akihiro; Takahashi, Nobuyuki; Tanabe, Kazuaki
<x xml:space="preserve">Abstract</x> Background Left atrial volumes (LAVs) have been suggested to represent long‐term exposure to elevated pressures. This study examined the recurrence of heart failure (HF) based on LAV in patients initially diagnosed with congestive HF (CHF). Methods This study comprised 77 patients (age, 75 ± 8 years) with well‐documented, clinically defined HF, and complete two‐dimensional echocardiographic examinations. The echocardiographic examinations were performed on admission and after medical treatment (90 ± 43 days after initial examination). Patients with atrial fibrillation, flail mitral valve, or mitral valve replacement were excluded from this study. Results The initial left ventricular ejection fraction (LVEF) was 44 ± 17% and the indexed LAV (LAVI) was 61 ± 22 mL/m2. After medical treatment, a decreased LAVI was observed in 38 patients and an increased LAVI (LA remodeling) was observed in 39 patients. With median follow‐up periods of 454 days, compared to patients with decreased LAVI, patients with LA remodeling had a significantly higher incidence of CHF recurrence (P = 0.008). Patients with LA remodeling had a CHF‐free survival rate of 36 ± 13% vs. 81 ± 9% (those without LA remodeling). A multivariate analysis indicated that, follow‐up LV end‐systolic volume (P = 0.04), LVEF (P = 0.005) and LAVI (P = 0.04) independently predicted CHF recurrence. Conclusions Patients initially diagnosed with CHF follow divergent courses based on their LAV. LA remodeling after medical treatment can be useful for predicting CHF recurrence during follow‐up.